COVID-19: how much unemployment was caused by the shutdown in Germany?. Issue 12 (12th July 2021) - Bauer, Anja; Weber, Enzo
ABSTRACT: This paper evaluates the short-term labour market impact of the COVID-19 containment measures in Germany. By assessing the treatment effect on unemployment via difference-in-difference estimation, we find that 60% of the considerably increased inflows from employment into unemployment in April 2020 were due to the shutdown measures. Disentangling further, we find that the hiring margin accounted for additional 82% of the unemployment effect coming from the separations margin. In sum, the shutdown measures increased unemployment in the short run by 117, 000 persons.